Sikap Politik pemerintah Dalam Perwacanaan Musik Populer tahun 80-an dan 90-an - Ashaf, Abdul Firman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2006)
The Booming of music industry in 1980a and allows Indonesian artist to again ample space for cultural expression.Yet, the state unwiling to accept the expressiin which given it own interest.